PENGARUH MEDIA FLIPBOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN PADA SISWA KELAS II SEKOLAH DASAR DI KECAMATAN DUREN SAWIT - Anadya Puspita Vania; Otib Satibi Hidayat (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to determine the effect of using flipbook media in improving early reading skills in grade II elementary school students in Duren Sawit District. The research method used is quantitative method with experimental type, with Pretest-Posttest Control Group Design. The samples in this study were grade II B students (30 students) as the control group and grade II C students (30 students) as the experimental group at SDN Duren Sawit 13, East Jakarta. Sampling using Simple Random Sampling technique. Data collection used, namely test techniques to measure the beginning reading skills of grade II students. The data analysis technique to test the hypothesis using the Independent Sample t Test obtained a significance level of 0.044, where 0.044 <0.05. So it can be concluded that H0 is rejected and H1 is accepted. The result of this research hypothesis is that there is an effect of using flipbook media on the ability to read beginning grade II elementary schools in Duren Sawit sub-district. This is based on the average at the time of the pretest of 65.83 and the average at the time of the posttest of 80.67.